Gendering caste: through a feminist lens - Chakravarty, Uma (Stree, 2003)
Examining the crucial linkages between caste and gender, undertaken, perhaps, for the first time, Uma Chakravarti unmasks the mystique of consensus in the workings of the caste system to reveal the underlying violence and coercion that perpetuate a severely hierarchical and unequal society. The subordination of women and the control of female sexuality are crucial to the maintenance of the caste system, creating what feminist scholars have termed brahmanical patriarchy. She discusses the range of patriarchal practice within the larger framework of sexuality, labour and access to material resources, and also focuses on the centrality of endogamous marriages that maintain the system. Erudite yet accessible, this book enables the reader to understand the interface of gender and caste and to participate in its critical analysis.